2010
DOI: 10.1136/jnnp.2010.210559
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early cognitive-linguistic treatment and communicative treatment in aphasia after stroke: a randomised controlled trial (RATS-2)

Abstract: This study does not confirm the hypothesis that patients with aphasia after stroke benefit more from CLT, aimed at activation of the underlying semantic and phonologic processes, than from general, non-specific communicative treatment (ISRCTN67723958 Current Controlled Trials).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
0
38
0
2
Order By: Relevance
“…particularly when considering the delicate nature of very early stroke recovery 1,4 and limitations in service delivery that many speech pathology services report. 24 Positive effects have been found from very early aphasia therapy in two small clinical randomised controlled trials 19,20 and from two trials in early recovery 25,26 . Yet few if any studies have included the amount of aphasia therapy in early aphasia recovery as a possible predictor in models of improved communication outcomes in post-stroke aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…particularly when considering the delicate nature of very early stroke recovery 1,4 and limitations in service delivery that many speech pathology services report. 24 Positive effects have been found from very early aphasia therapy in two small clinical randomised controlled trials 19,20 and from two trials in early recovery 25,26 . Yet few if any studies have included the amount of aphasia therapy in early aphasia recovery as a possible predictor in models of improved communication outcomes in post-stroke aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…После перенесен-ного инсульта пациент, как правило, страдает не только от когнитивных расстройств, но и от эмоционального состоя-ния. Систематические клинические наблюдения [9] и сле-пые рандомизированные мультицентровые исследования [10] показывают, что работу с пациентами в остром пери-оде надо начинать с оказания психологической поддерж-ки, информирования и обучения пациента и его родствен-ников компенсаторным коммуникативным стратегиям. Это сформирует понимание ситуации и облегчит коммуника-цию между пациентом и окружающими его людьми.…”
Section: коррекция речевых расстройствunclassified
“…While preliminary research for early aphasia intervention has shown positive results (de Jong-Hagelstein et al 2011;Godecke et al 2012;Sickert et al 2013) there is no evidence (Brady et al 2012) to support the efficacy of very early post-stroke aphasia treatments in the long-term. This is a result of limitations in study methodology, difficulties with participant selection, reduced sample size, inconsistent application and description of aphasia therapy types and use of low intensity aphasia rehabilitation.…”
Section: Limitations Of Existing Aphasia Research and Future Researchmentioning
confidence: 99%